Inferring Intentions from Consequences: How Moral Judgments Shape Citizen Perceptions of Wartime Conduct. Issue 2 (18th September 2021) - Chu, Jonathan A.; Holmes, Marcus; Traven, David
Abstract: How people interpret the intentions of others is fundamental to politics. This article examines intention understanding in the domain of how citizens evaluate wartime conduct. Drawing on recent work in moral psychology, it argues that people are more likely to attribute intentionality to wartime actions that produce morally bad consequences than otherwise identical actions that produce morally good consequences. We test this theory with two vignette-based survey experiments. Our results show that this hypothesis holds in a variety of contexts relating to civilian casualties and the destruction of heritage sites during war. By unlocking the moral psychology of intention understanding, this article contributes to the field of political psychology in general, and more specifically to theoretical debates in International Relations (IR) about public opinion on just war doctrine.